(untitled) (Cadernos de Sociomuseologia, 2025)
The article addresses a current paradox within the museum sector, which increasingly embraces “communities” as part of its renewed commitment to social inclusion and co-creation, whilst often lacking the professional skills and ethical parameters required in collaborative work. The discussion examines examples from the UK to trace how the term “community” has migrated from aspirational international policies and codes of ethics to inform new collective practices across museums of different kinds. By exploring the multiple ways in which museums and communities nurture one another, the article considers how collaboration has been practised under emerging ethical imperatives – particularly those involving care work and the negotiation of power imbalances that frequently arise in such exchanges. The redistribution of authority between communities and professionals is highlighted as a persistent challenge in developing a truly collective expertise founded on knowledge-sharing and mutual understanding. The concept of “community sovereignty” is introduced to articulate a sociomuseological shift in power: one that frames the community as a form of political imagination capable of mobilising action. In conclusion, the article draws on the framework of social museology to conceive some basic principles for a relational ethics. Keywords: Communities; Social Museology; Museum Profession; Museum Ethics